The Role of Labor Law in Settling Industrial Relations Disputes: A Normative Juridical Perspective on the Rights of Workers and the Obligations of Employers in Indonesia - Rahmawati, Diah Ayu; Haryono, Haryono; Endarto, Budi; Nuroini, Indi; Hananto, Hananto (West Science Law and Human Rights, 2025)
This research reviews labor law's role in the settlement of disputes in industrial relations within a normative juridical perspective in Indonesia. The research focuses on workers' rights and employers' obligations under Indonesia's labor legislation, mainly Undang-Undang No. 13 Tahun 2003 (the Labor Law). The study examines dispute resolution mechanisms, such as negotiation, mediation, and arbitration through the PHI, their effectiveness in protecting workers' rights, and how well employers adhere to the law. From the results, it is learned that negotiation and mediation are effective at the starting stage, but due to power imbalance and delayed processing in the judicial system, comprehensive settlements could not be achieved. Moreover, inconsistent court decisions, weak enforcement of workers' rights, and lack of adequate union representation remain critical. Concluding, the paper provides recommendations on how Indonesia can better settle labor disputes by strengthening mechanisms for mediation and arbitration, enhancing judicial capacity, and effective enforcement of workers' rights.